High tumor mutational burden (TMB) identifies a microsatellite stable pancreatic cancer subset with prolonged survival and strong anti-tumor immunity. (July 2022) - Karamitopoulou, Eva; Andreou, Andreas; Wenning, Anna Silvia; Gloor, Beat; Perren, Aurel
Abstract: Aim: Tumor mutational burden (TMB: somatic mutations per megabase, mut/Mb) predicts the efficacy of immunotherapy. Here, we link TMB levels with the activation of immune pathways and intratumoral immune responses in pancreatic adenocarcinoma (PDAC) to explore immunoarchitectural patterns associated with high TMB. Methods: We assessed TMB in 161 resected, microsatellite stable (MSS) PDACs, including 41 long-term survivors (LTS). Five microsatellite instable (MSI-high) cases were also assessed. Cases were classified into TMB-high (≥10 mut/Mb), TMB-intermediate (>5 < 10 mut/Mb), and TMB-low (≤5 mut/Mb) categories. Tumors additionally underwent mRNA in situ hybridization for immune pathway genes and were immunoprofiled by multiplex immunofluorescence followed by automated image analysis. Results: We detected 12 TMB-high, 28 TMB-intermediate, and 121 TMB-low cases. TMB-high tumors comprised ten LTSs (10/41; 24%) and two conventional PDACs (2/120; 1.7%). They exhibited the highest T cell density with significantly increased CD3 + CD4 + T helper and CD208 + dendritic cell (DC) counts, compared to all other cases. CD3 + CD8 + cytotoxic T cells were significantly closer to tumor cells and T helper cells closer to DCs in TMB-high PDACs. Immune pathways involved in T cell activation, immune cell adhesion/migration, antigen presentation, and cytokine signaling were upregulated in most TMB-high and many TMB-intermediate tumors. ARID1A and ERBB4 alterations were more frequent in TMB-high PDACs. All MSI-high PDACs were TMB-high. Conclusions: TMB-high cases frequently belong to specific PDAC subsets with prolonged survival such as LTSs and MSI-high PDACs. They display strong anti-tumor immune responses fueled by a T helper cell/DC-mediated priming of the cytotoxic T cells. Moreover, they frequently harbor further actionable alterations. Graphical abstract: Image 1 Highlights: TMB-high cases frequently belong to specific PDAC subsets with prolonged survival. They show distinct immuno architectural patterns and "hot" immune microenvironment. Their anti-tumor response is fueled by a Th/DC priming of the cytotoxic T cells. TMB-high PDACs frequently harbor further actionable alterations.